\(6x^2y^4+3x^2-10y^3=-2\)
\(\Leftrightarrow3x^2\left(2y^3+1\right)-10y^3-5+5=-2\)
\(\Leftrightarrow3x^2\left(2y^3+1\right)-5\left(2y^3+1\right)=-7\)
\(\Leftrightarrow\left(3x^2-5\right)\left(2y^3+1\right)=-7\)
\(\Rightarrow\left(3x^2-5\right);\left(2y^3+1\right)\in\left\{-1;1;-7;7\right\}\)
\(\Rightarrow\left(x;y\right)\in\left\{\left(\pm\dfrac{2}{\sqrt[]{3}};\sqrt[3]{3}\right);\left(\pm\sqrt[]{2};\sqrt[3]{4}\right);\left(\varnothing;0\right);\left(\pm2;-1\right)\right\}\)
\(\Rightarrow\left(x;y\right)\in\left\{\left(\pm2;-1\right)\right\}\left(x;y\in Z\right)\)
6x2y3 +3x2 - 10y3 = -2
\(_{_{ }^{ }\Leftrightarrow}\) 2y3(3x2 \(-\) 2) + 3x2 \(-\) 2= -4
\(_{_{ }^{ }\Leftrightarrow}\)\(\left(3x^2-2\right)\left(2y^3+1\right)=-4=-1.4=-2.2\)
Vì x2 \(\ge\)0 nên 3x2 -2 \(\ge\)-2
Ta có các trường hợp:
TH1: \(\left\{{}\begin{matrix}3x^2-2=-1\\2y^3+1=4\end{matrix}\right.\)\(\Leftrightarrow\)\(\left\{{}\begin{matrix}x=\pm\dfrac{1}{\sqrt{3}}\\y=\sqrt[3]{\dfrac{3}{2}}\end{matrix}\right.\)
TH2: \(\left\{{}\begin{matrix}3x^2-2=2\\2y^3+1=-2\end{matrix}\right.\)\(\Leftrightarrow\)\(\left\{{}\begin{matrix}x=\pm\dfrac{2}{\sqrt{3}}\\y=\sqrt[3]{\dfrac{-3}{2}}\end{matrix}\right.\)
TH3: \(\left\{{}\begin{matrix}3x^2-2=-2\\2y^3+1=2\end{matrix}\right.\)\(\Leftrightarrow\)\(\left\{{}\begin{matrix}x=0\\y=\sqrt[3]{\dfrac{1}{2}}\end{matrix}\right.\)
Vậy .....